Distribution and relative abundance of the economically important click beetles (Elateridae: Agriotes sp.) in Hungary - Nagy, Antal; Dávid, István; Szarukán, István (Acta Agraria Debreceniensis, 2010)
Click beetle (Elateridae: Agriotes sp.) species of 24 sites in different regions of Hungary were studied in 2010. A. brevis, A. sputator, A. obscurus, A. lineatus, A. rufipalpis and A. ustulatus were sampled by pheromone traps in maize fields. During the study more than 80000 beetles were caught. The three most common species were A. ustulatus, A. sputator and A. rufipalpis. The distribution of the studied species was uneven. In south Hungary A. ustulatus, A, rufipalpis and A. sputator were the three most abundant species. In the Transdanubia A. sputator was the most abundant. A. ustulatus reached higher abundance in only three sites (3/12). A. obscurus occurred only in west Hungary (Transdanubia). In eastern Hungary the abundance of studied species was higher. In this reason we have to monitor the populations of these pests and if it is necessary we have to take actions against them. In Transdanubia the abundance were generally lower but in many cases reached the threshold of significant damage. Beyond that 13 additional species were sampled so the total number of sampled species was 19.